2019
DOI: 10.1515/cclm-2019-0655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the primary biliary cholangitis-related serologic profile in a large cohort of Belgian systemic sclerosis patients

Abstract: BackgroundSystemic sclerosis (SSc) and primary biliary cholangitis (PBC) are autoimmune diseases that may occur concomitantly and are both strongly associated with disease-specific autoantibodies. This study investigated the prevalence and fine specificity of PBC-specific serology (PBC-Ab) and associations with the SSc-subtypes and SSc-specific antibodies as well as the association with cholestatic liver enzymes. Furthermore, three different techniques for the detection of PBC-Ab were compared.MethodsSerum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…Our data agree with previous studies, confirming a significant higher prevalence of ACA in PBC-SSc patients compared to subjects with SSc alone. This datum seems to be in accordance with results from a recent study of Florin et al 31 that showed a strong correlation of different PBCspecific antibodies and ACA and not with the limited cutaneous subset. These data suggest a probable crucial role of ACA in autoimmune disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data agree with previous studies, confirming a significant higher prevalence of ACA in PBC-SSc patients compared to subjects with SSc alone. This datum seems to be in accordance with results from a recent study of Florin et al 31 that showed a strong correlation of different PBCspecific antibodies and ACA and not with the limited cutaneous subset. These data suggest a probable crucial role of ACA in autoimmune disease.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, PBC-specific autoantibodies may be found in SSc patients also in the absence of cholestatic liver enzyme elevations probably preceding PBC development. 31 Another interpretation of these findings is that the link between SSc and PBC relates more strongly with autoimmunity rather with the severity of fibrosis as demonstrated by the association with the limited cutaneous subset and not with the diffuse one. This could give clues to some pathomechanisms involved in SSc-PBC subphenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ANA are not specific for PBC and are also present in patients with other immunological disorders and infections without elevated liver enzymes levels. [53,54] Although a possible molecular mimicry between the epitopic regions of E. coli and a nuclear protein Sp100 has been proposed on the basis of a strong correlation between the presence of anti-Sp100 antibodies and AMA positivity in women with recurrent UTI, direct evidence is lacking. [4] The mechanism underlying the induction and generation of ANA in PBC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature screened by our group, we selected 10 articles with relevant data support to make statistics and comparisons on the occurrence probability of clinical manifestations of anti-CENP-B positive SSc patients. As shown in Table 3-3, gastrointestinal involvement had the highest incidence of symptoms (46.44%) [35], followed by telangiectasia (45.25%) and Raynaud's phenomenon (44.23%) [36,37]. However, the data of different studies on these two phenomena were quite different, so the reliability was not high.…”
Section: Distribution Of Clinical Manifestations In Anti-cenp-b(+) Ssc Patientsmentioning
confidence: 99%